Discussion of AIGC Technology in a Photography Course at a Higher Vocational College - Wang, Fu (Journal of Research in Vocational Education, 2024)
This study explores the teaching strategies of photography courses at a higher vocational college in China, focusing on the application of Artificial Intelligence Generated Content (AIGC) technology, specifically Stable Diffusion. Utilising the AI-TPACK theory as a theoretical framework, data were collected from teachers and students through 1) observation, 2) semi-structured interviews, and 3) focus group discussions. The researcher analysed the data using a phenomenological approach to capture the following core themes: 1) practical photography skills, 2) innovation and efficiency in post-processing, and 3) exploration of personalised styles and creative thinking. The results of this study contribute to the ongoing development of photography courses in higher vocational colleges amid technological innovation, demonstrate the positive effects of AIGC technology on enhancing the quality of photography teaching and creativity, and provide both theoretical support and practical guidance for curricular reform and teaching strategies.